SOSIALISASI MANFAAT SENAM YOGA PADA LANSIA: SOCIALIZATION OF THE BENEFITS OF YOGA EXERCISE IN THE ELDERLY - Yestiani Norita Joni; Safitri.E (Jurnal Pengabdian Masyarakat Kesosi, 2020)
Changes in cognitive function in the elderly cause a shift in the role of the elderly in social interaction in the community and in the family. Another change experienced by the elderly is a decline in cognitive abilities. Based on the results of previous studies stated that one alternative therapy that can be given to improve the cognitive abilities of the elderly is to do yoga. The objectives of this socialization activity include: 1) Providing motivation to partner communities in increasing care for the elderly, 2) The ability and success of partner communities depends on family participation in caring for and dealing with family members. The number of participants who were successfully recorded was based on the attendance list of 15 people. This activity was initiated by providing socialization about the benefits of yoga exercise, then continued by providing a demonstration of the implementation of yoga exercise.